Testing loan loss provisioning hypotheses for banks from the U.S. - Tong, Yushang (2018)
This research examined Loan Loss Provisions (LLP) determinants: income smoothing, capital management, business cycle and cost X-efficiency, using 150 US commercial and saving banks from 2011 to 2017 with the use of stochastic frontier analysis (SFA) and two- step system Generalized Method of Moments (GMM) estimation. To test the impact of efficiency on LLP, the first stage is carried out generating cost efficiency scores for individual banks in each year using cost translog function. The second stage then tests the determinacy of LLP using main determinants variables via the GMM model. Following Bryce et al. (2015), I have tested four hypotheses, which are income smoothing hypothesis business cycle hypothesis, capital management hypothesis and cost efficiency. Empirical results support counter-cyclical and income smoothing however fail to support capital management and cost efficiency.